THE ROLE OF DIGITAL-BASED EVALUATION IN IMPROVING LEARNING OUTCOMES - Simamora, Yericho Lam Pedro; Saptono, Ari; Pratama, Aditya (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
The purpose of this research is to determine the extent to which digital-based evaluation methods combined with learning motivation are capable of influencing the economics learning achievement for high school students at SMA Negeri 53 Jakarta. The experiment was conducted by a quasi-experimental design. Two classes were selected, one consisting of students who were assessed using the digital assessment method of Quizizz platform while the other was taught using the conventional methods of assessment. The interventions included a pre-test and post-test measurements, and a learning motivation scale was also given to the students. The ANOVA results showed that there was a better level of economics learning outcomes between the digital based and conventional evaluation methods. There was also found a significant interaction of evaluation method and motivation level on learning outcomes, meaning that when students are highly motivated to learn subjects like economics, performance is best with the help of digital tests. These results encourage the use of digital assessment methods as a remedy to improve the learning of economics